2019
DOI: 10.24248/eahrj.v3i2.607
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Cervical Cancer Screening Services and Its Association with Cervical Cancer Awareness and Knowledge Among Women of Reproductive Age in Dodoma, Tanzania: A Cross-Sectional Study

Abstract: Background: There is a close link between an individual's knowledge about a given disease and uptake of screening and ultimately treatment. This study aimed to determine the link between knowledge levels and awareness and uptake of cervical cancer screening among women of reproductive age (15 to 49 years) in Dodoma, Tanzania. Methods: A cross-sectional study of 1,587 women aged between 15 and 49 years was conducted in Dodoma City, Tanzania. A structured questionnaire, adapted from Montgomery and others, was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
5
1
Order By: Relevance
“…We attribute this finding to the availability of screening campaigns and daily VIA clinics at the district hospital, a scenario that is not common in health facilities in the rural areas. A Tanzanian study done by [30] supports this notion as women residing in urban areas were found to be more likely to be knowledgeable about CC than their counterparts who lived in the rural areas. They had affirmed that women in the urban areas had more access to health information through media and they had easy access to the health facilities.…”
Section: Discussionmentioning
confidence: 94%
“…We attribute this finding to the availability of screening campaigns and daily VIA clinics at the district hospital, a scenario that is not common in health facilities in the rural areas. A Tanzanian study done by [30] supports this notion as women residing in urban areas were found to be more likely to be knowledgeable about CC than their counterparts who lived in the rural areas. They had affirmed that women in the urban areas had more access to health information through media and they had easy access to the health facilities.…”
Section: Discussionmentioning
confidence: 94%
“…When looked at the African continent, very diverse findings were also reported. According to the Tanzania study, only 10.4% of women were knowledgeable about cervical cancer and 7.9% of these were screened [ 36 ] which was very low. Similarly, in Nigeria18.1% of them had good knowledge with 67.8% of them to have a positive attitude to cervical cancer screening [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Tanzania study, only 10.4% of women were knowledgeable about cervical cancer and 7.9% of these were screened [ 36 ] which was very low. Similarly, in Nigeria18.1% of them had good knowledge with 67.8% of them to have a positive attitude to cervical cancer screening [ 37 ]. In Uganda and Burkina-Faso, the two studies reported that only 4.8% and 11.1% of women had been screened for cervical cancer, respectively [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there no association between the demographic factors and knowledge of risk factors and symptoms, probably because the population was generally uniform with no signi cant differences with regard to their demographic characteristics and knowledge of cervical cancer. This is unlike other studies where low knowledge of risk factors was associated with not being married [25] and low education [26]. In another study the level of education was associated with high knowledge for risk factors while older age was associated with symptom awareness [27].…”
Section: Knowledge On Cervical Cancermentioning
confidence: 57%